Supporting Factors of Digital Marketing and Customer Relationship Management and Their Role in Developing the Champion UMKM Model in West Java: Literature Review - Wulandari, Rosanna; Nugroho, Arissetyanto; Derriawan, Derriawan (Quantitative Economics and Management Studies, 2025)
This study aims to identify the supporting factors in implementing Digital Marketing(DM) and Customer Relationship Management(CRM) and to examine their role in developing the Champion MSME model in West Java. Amidst tight digital competition, many MSMEs have not fully leveraged the use of digital technology, particularly in building strong customer relationships and expanding their market share. The method employed is a Systematic Literature Review(SLR) using the PRISMA 2020 guidelines, which involves articles published between 2015 and 2025 and indexed in Scopus, Web of Science, Copernicus, Sinta, and Garuda. The results of the study show that the success of digital marketing (DM) and CRM depends on the level of digital literacy, technological infrastructure support, personal interaction, and efficient customer data management. Both strategies play a role in increasing Customer Satisfaction(CS), Customer Engagement(CE), and Customer Loyalty(CL), which then contribute positively to MSME performance. In addition, the Soft System Methodology (SSM) approach is used to design a contextual Champion MSME development model that involves the participation of stakeholders. These findings are expected to be the basis for an effective strategy for developing sustainable MSME digitalization.